Actualización del manejo de metástasis encefálicas - Zomosa R., Gustavo; González J., Lucas; Miranda G., Gonzalo; Galleguillos E., María Fernanda; Arellano A., Anita (Revista Hospital Clínico Universidad de Chile, 2018)
rain metastases represent a critical stage of oncological disease and its frequency isincreasing over the recent years. The treatment of brain metastases has moved from aconservative approach to an active management that should be individualized for each patient:in case of single brain metastasis, surgery or radiosurgery should be considered as first optionof treatment; in case of multiple lesions, whole-brain radiotherapy is the standard of care. Theaim of this review is to present general aspects including new approaches in management ofpatients with brain metastases.